Emosi Dalam Novel Kasrimpet Piweling Karya Tulus Setiyadi (Teori Psikologi Allport) - Anggraini, Winda; Andriyanto, Octo Dendy (Jurnal Online Baradha, 2023)
Abstract Allport's theory uses several terms that are considered important, namely traits, attitudes, and habits. Of these three can determine the emotions of every human being. Emotions are prejudices that arise when humans are in certain situations. The purpose of this research is The form of emotion experienced by the characters. The method used is qualitative in the form of a description. The source of the data in this study was the novel Kasrimpet Piweling by Tulus Setiyadi and the data collected in this panel were in the form of words, phrases and sentences. The instrument in this study was the researcher herself in analyzing the novel, also assisted by supporting tools in the form of laptops, novels, books, and stationery used to record and store the data found. Collecting research data by way of literature study. The data analysis technique used is descriptive qualitative analysis. The results of this study are divided into two, namely The Emotional Forms experienced by the Characters, divided into three, namely confusion, love, and disappointment. Keywords: Allport Psychology, Structure of Personality, Emotional form.AbstrakTeori Allport menggunakan beberapa istilah yang dianggap penting yaitu sifat, sikap, dan kebiasaan. Dari ketiga tersebut dapat menentukan emosi setiap manusia. Emosi yaitu prasangka yang timbul ketika manusia berada di situasi tertentu. Tujuan dari penelitian ini yaitu wujud emosi yang dialami tokoh. Metode yang digunakan yaitu kualitatif yang berupa deskripsi. Sumber data dalam penelitian ini berupa novel Kasrimpet Piweling karya Tulus Setiyadi dan data yang dikumpulkan dalam panliten ini berupa kata, frasa lan kalimat. Instrumen dalam penelitian ini yaitu peneliti sendiri dalam menganalisis novel, juga dibantu alat-alat pendukung berupa laptop, novel, buku, dan alat-alat tulis yang digunakake untuk mencatat dan menyimpan data-data yang ditemukan. Mengumpulkan data penelitian dengan cara studi pustaka. Teknik analisis data yang digunakan yaitu analisis dekriptif kualitatif. Hasil penelitian ini dibagi menjadi dua yaitu Wujud Emosi yang dialami oleh tokoh, dibagi menjadi tiga yaitu bingung, cinta, dan kecewa.Kata Kunci : Psikologi Allport, Struktur Kepribadian, Wujud Emosi.